Phytochemical and Pharmacology Effect of Calotropis gigantea as Anti-Cancer Therapy: Systematic Review - Mutiah, Roihatul; Ramzi, Humaira; Bustami, Jesi Aulia (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2021)
The high prevalence of cancer in the world makes many researchers look for alternative therapies that can be used to treat cancer. One of them is by using traditional plants, namely Calotropis gigantea R.Br. This is due to alkaloids, glycosides, and tannins in plants that function as anticancer. The purpose of this study was to dig deeper into information related to the phytochemistry and pharmacology effect of Calotropis gigantea as an anticancer therapy and can be used as a reference for the development of traditional medicines. The method used is PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta-analyses ), with inclusion and exclusion criteria, 11 articles were selected for review. The results showed that Calotropis Gigantea contains Calotropin, Calotroposide A, oxypregnane oligoglycoside compounds, which inhibit cancer cell growth through the mechanism of apoptosis induction and ROS inhibition. From this systematic review, it can be recommended that the plant  Calotropis gigantea can be further developed into standardized herbal medicine and phytopharmaceuticals.